Adverse childhood experiences and mental and physical health disparities: the moderating effect of race and implications for social work. (13th September 2020) - LaBrenz, Catherine A.; O'Gara, Jaimie L.; Panisch, Lisa S.; Baiden, Philip; Larkin, Heather
ABSTRACT: Adverse childhood experiences (ACEs) have been linked to mental and physical health problems, leading to ACEs being viewed as a public health concern. Yet, less research has focused on the prevalence and impact of ACEs among diverse racial and ethnic groups. Given the increasing diversity in the USA, coupled with research that has found certain racial and ethnic groups to experience larger-scale adversity such as poverty or discrimination more frequently than White individuals, it is important to understand how ACEs are experienced by people of color. The current study examined the prevalence of ACEs among diverse racial and ethnic groups, and associations between ACE score and mental and physical health. Even after adjusting for sociodemographic factors, ACE scores of 3 or higher were linked to more physical and mental health problems. Furthermore, there was a significant interaction effect between ACE score and race on mental health, while none of the interaction terms were significant between ACE score and race on physical health. This suggests that higher ACE scores have a more detrimental impact on mental health for people of color. Implications for social work include implementing community-level ACE-informed responses, especially in communities that serve traditionally marginalized populations.